Philosophy of recontextualization, recontextualization of philosophy. General remarks - Kwiek, Marek (Wydawnictwo Naukowe IF UAM, 1996)
Let us begin our more detailed discussions with a rather general chapter that is an attempt to get close to Richard Rorty’s philosophical discourse on as broad a plane as possible and with a brief and introductory analysis of certain themes, questions and issues present in his recent books. Thus this will be a chapter not so much introducing to a wider context but rather introducing to Rorty’s thought itself. In the next chapters there will appear in the form of more detailed analyses, reconstructions, redescriptions and readings some questions incidentally and generally put here in this chapter. The first volume of Rorty’s Philosophical Papers (1991) is devoted, for the most part, to the philosophers from the analytic circle, whereas the second to the figures and questions at the heart of which lie the works of Nietzsche, Heidegger, Wittgenstein, Derrida and Foucault. It causes some noticeable tension between the two volumes but the links between them are created by "pragmatism" (and "liberalism"), strongly stressed and still clarified by Rorty. The first volume is shadowed mainly by one philosopher - Donald Davidson. Whereas when Rorty was writing his Philosophy and the Mirror of Nature, the first and extremely influential book, he was strongly influenced, as he admits himself, by Wilfrid Sellars and W.v. O. Quine, during the next decade (in the eighties) it was Donald Davidson that impressed him most and affected his philosophizing to the greatest extent. "I have been writing - explains Rorty - more and more about Davidson - trying to clarify his views to myself, to defend them against actual and possible objections, and to extend them into areas which Davidson himself has not yet explored". Also in his Contingency, Irony, and Solidarity - the book which seems to use the knowledge and experience of a multitude of texts from the collection of Philosophical Papers (and to which Rorty refers the reader as to its exemplification and a more detailed description), and perhaps a crystallization of these articles - he sees Davidson as an absolutely crucial figure for his own considerations, especially those devoted to language, relations between language and reality, created truth rather than discovered one and so on. As is commonly known, Davidson is an antirepresentationalist and antiessentialist, he rejects the notion of language as some medium, as the third thing, intruding between the self and the reality. Knowledge, both to Rorty and to Davidson as well, is not a matter of getting reality right but rather a matter of "acquiring habits of action for copying with reality", as the former puts it.
Keywords: Richard Rorty; neopragmatism; American pragmatism; new pragmatism; liberal ironist; redescription; recontextualization; Contingency, Irony, and Solidarity; What is Pragmatism; Consequences of Pragmatism; Philosophy and the Mirror of Nature; postmodernism; American philosophy; John Dewey; Donald Davidson; truth; antiessentialism; objectivity; Nietzsche; Wittgenstein